Jurnal Pengaruh Jumlah Penduduk, Tingkat Upah Minimum dan Tingkat Pengangguran Terhadap Pengeluaran Perkapita Kabupaten/Kota Provinsi Sumatera Utara_Bungaran Silalahi & Dede Ruslan - Silalahi, Bungaran; Ruslan, Dede (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2024)
Per capita expenditure is an important indicator reflecting the purchasing power and welfare of a country or region. This study aims to describe per capita expenditure in North Sumatra Province at the district/city level and analyze the influence of population, minimum wage, and unemployment rate on per capita expenditure across all districts/cities in North Sumatra Province in 2022. This study uses a quantitative method with a cross-sectional data regression model, accompanied by tests for normality, multicollinearity, heteroscedasticity, autocorrelation, and hypothesis testing. The results of the analysis indicate that the minimum wage level has a significant effect on per capita expenditure, while population and unemployment rate do not. The results of this study are expected to serve as a reference for local governments in formulating policies that support increased per capita expenditure, which ultimately contributes to encouraging consumption and driving the regional economy.